Treatment of myofascial pain syndrome with lidocaine injection and physical therapy, alone or in combination: a single blind, randomized, controlled clinical trial (2016)
ABSTRACT: Background Myofascial pain syndrome (MPS) of the shoulder girdle and cervical region is a common musculoskeletal problem that is often chronic or recurrent. Physical therapy (PT) and lidocaine injections (LI) are two treatments with demonstrated effectiveness compared to a control group, however little is known about their combined value. The objective of this study was to determine whether LI into trigger points combined with a PT program would be more effective than each separate treatment alone in improving pain, function, and quality of life in a group of patients with MPS of the shoulder girdle and cervical region. Methods A single-blind, randomized, controlled clinical trial (RCT) was conducted with three parallel groups in the Departments of Physical Medicine and Rehabilitation of two urban hospitals in Medellin, Colombia. One hundred and twenty seven patients with shoulder girdle MPS for more than 6 weeks and pain greater than 40 mm on the visual analog scale (VAS) were assigned to 1 of 3 intervention groups: PT, LI, or the combination of both (PT + LI). The primary outcome was VAS pain rating at 1-month post-treatment. The secondary outcomes included VAS pain rating at 3 months, and, at both 1 and 3 months post-treatment: (a) function, evaluated by hand-back maneuver and the hand-mouth maneuver, (b) quality of life, as measured by sub-scales of the Short Form – 36 (SF-36), and (c) depressive symptoms, as measured by the Patient Health Questionnaire – 9 (PHQ-9). Independent t-tests were used to compare outcomes between groups at 1 month and 3 months post-treatment. Results In the per protocol analysis, there were no significant intergroup differences in VAS at 1 month PT + LI, 40.8 [25.3] vs. PT, 37.8 [21.9], p = 0.560 and vs. LI, 44.2 [24.9], p = 0.545. There were also no differences between groups on secondary outcomes except that the PT and PT + LI groups had higher right upper limb hand-back maneuver scores compared to the LI alone group at both 1 and 3 months (p = 0.013 and p = 0.016 respectively). Conclusions The results of this RCT showed that no differences in pain ratings were observed between the individual treatments (PT or LI) compared to the combined treatment of PT and LI. In general, no difference in primary or secondary outcomes was observed between treatments.